AUDIT KINERJA GURU DAN KEPALA SEKOLAH DI SMP MA'ARIF MIFTAHUL ULUM BUNGAH - Tria Heni Agustina; Amrozi Khamidi; Kaniati Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Republic of Indonesia Government Regulation Number 19 of 2005 concerning National Education Standards, article 2 paragraph 2, namely to guarantee and control the quality of education in accordance with national education standards, evaluation, accreditation and certification are carried out (President of the Republic of Indonesia, 2005). School Supervisors as functional technical implementers in the field of academic and managerial supervision in a number of designated educational units and have the main tasks of academic and managerial supervision, evaluation and auditing. Based on the audit results of the target school, Ma'arif Miftahul Ulum Middle School (foundation type institution), with the scope of academic and managerial audits in 2024. The main focus is the findings related to the results of the identification and analysis of the previous year's audit, the performance results of teachers and school principals rose to: predicate B "Good". The purpose of the audit is to obtain accurate information about the successes and problems faced by the audit targets, namely school principals, teachers, education staff and target schools. The research uses qualitative research methods with a contextual approach such as auditing with interviews, observation and documentation. Audit method with managerial aspect: FGD, and academic aspect: individual-group technique. Data collection steps: compiling and preparing learning and management audit instruments which have been provided in the form of a checklist. Data analysis technique: presentation of findings that have been assessed qualitatively. The audit results contained deficiencies: (1). the majority of teachers do not understand pedagogical and professional competence in preparing learning administration, (2) teachers lack the ability to use learning technology media, (3) teachers do not understand how to arrange teaching materials, (4) lack of infrastructure. Keywords: audit, teacher performance, school principal